THE EFFECT OF PRESORBED WATER ON THE ADSORPTION OF CFC-113 BY A CARBON ADSORBENT - CHO, SY (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
The adsorption experiments of 1,1,2-trichloro-2,2,1-trifluoroethane on dry activated carbon pellet were carried out at 298 K. For low concentrations of 1,1,2-trichloro-2,2,1-trifluoroethane; the Langmuir equation was well correlated by experimental data. In this study, the effects of presorbed water upon the adsorption capacity of 1,1,2-trichloro-2,2,1-trifluoroethane by a pellet-type carbon adsorbent are considered. It was found that the large decrease in adsorption capacity was caused by the presorbed water.
Keywords: CHLOROFLUOROMETHANES; DESTRUCTION; OZONE